Reconstructing the landscapes of slavery : a visual history of the plantation in the nineteenth-century Atlantic world - Tomich, Dale W., 1946-; Tomich, Dale W. (Chapel Hill : The University of North Carolina Press, 2021)
"Assessing a unique collection of more than eighty images, this innovative study of visual culture reveals the productive organization of plantation landscapes in the nineteenth-century Atlantic world. These landscapes-from cotton fields in the Lower Mississippi Valley to sugar plantations in western Cuba and coffee plantations in Brazil's Paraíba Valley-demonstrate how the restructuring of the capitalist world economy led to the formation of new zones of commodity production. By extension, these environments radically transformed slave labor and the role such labor played in the expansion of the global economy"--
Includes bibliographical references and index.
Keywords: Plantations -- Mississippi River Valley -- History -- 19th century; Plantations -- Cuba -- History -- 19th century; Plantations -- Brazil -- Paraibuna River Valley -- History -- 19th century; Plantations -- Mississippi River Valley -- Pictorial works; Plantations -- Cuba -- Pictorial works; Plantations -- Brazil -- Paraibuna River Valley -- Pictorial works; Slavery -- Economic aspects -- Mississippi River Valley; Slavery -- Economic aspects -- Cuba; Slavery -- Economic aspects -- Brazil -- Paraibuna River Valley